Two new species of Empis (Planempis) from Oriental China, with an updated key to species of China (Diptera: Empidoidea) - Liu, Xiaoyan; Saigusa, Toyohei; Yang, Ding (Zootaxa, 2012)
Two species, Empis (Planempis) tianmushana sp. nov. and E. (P.) zhuae sp. nov., from Zhejiang province of OrientalChina are described as new to science. An updated key to the known species of the subgenus Planempis from China is presented.